Analisis Sistem Ekonomi Kerajaan Aceh Darussalam pada Masa Pemerintahan Sultan Iskandar Muda - Yeyen Novita; Mochlasin Mochlasin; Shindita Apriliani Nirmalasari; Salman Zakki Syahriel Mubarok; Angga Dwi Febrianto; Ahmad Ulil Albab Al Umar (Journal on Education, 2023)
Aceh is the first place where the spread of Islam took place in the archipelago, so it is called the door to the spread of Islam. Evidence of the spread of Islam in Aceh is the establishment of Islamic kingdoms such as the Kingdom of Perlak, Samudra Pasai and Aceh Darussalam. The policies of the kings also became the forerunner of activities that are still carried out today. In addition, there are also the thoughts of scientists which are then used as a sign of scientific progress that continues to be perfected. The purpose of this study was to find out how the economic system of the Aceh Darussalam kingdom was during the reign of Sultan Iskandar Muda. This study uses a qualitative method with a historical approach. Sources of data obtained from relevant literature studies. The results of the study indicate that the reign of Sultan Iskandar Muda succeeded in liberating and protecting Aceh from the colonial powers who wished to seize power over Aceh. This was done by implementing a price increase policy in which Sultan Iskandar Muda set prices and controlled the market from foreigners/colonizers. This made the invaders reluctant to attack the Aceh kingdom. The economic system of the Aceh kingdom is also very good with the advancement of trade from rural to urban areas.